Alone-Together Mediation in Correlation between Social Media Usage and Face-to-Face Communication of Millennials - Setiadi, Esseline; Alqadri, Andi Ilman; Devitoyani, Seruni Rami (Technium Social Sciences Journal, 2021)
The existence of social media has currently become a communication phenomenon, specifically occurring to millennials which is argued to allow Alone-Together to develop. Alone-Together is a phenomenon where a social media user loses focus of his or her surroundings thus concurrently distracting his or her face-to-face communication. This quantitative research was conducted in Indonesia through observation to millennials who were social media users of Facebook, Twitter and Instagram with age distribution ranging from 23 – 38 years old. S-O-R method was employed to reveal the correlation between social media and face-to-face communication mediated by Alone-Together. The result revealed that there was a correlation between social media usage with Alone-Together behavior and the influence of Alone-Together attitude toward face-to-face communication. However, no correlation was found between social media and face-to-face communication therefore it is concluded that this research is fully mediated. In addition to that, this research is expected to provide more contribution to further studies related to supporting variables in the current existence of social media, promoting the benefits of using social media, identifying limits which need further control in using social media and mitigating the impacts inflicted to their users.